OS 03-05 EFFECT OF SALT REDUCTION ON IODINE STATUS ASSESSED BY 24 H URINARY IODINE EXCRETION IN CHILDREN AND THEIR FAMILIES IN NORTHERN CHINA: A CLUSTER RANDOMISED CONTROLLED TRIAL. (September 2016) - He, Feng; Ma, Yuan; Feng, Xiangxian; Zhang, Wanqi; Lin, Laixiang; Guo, Xiaohui; Zhang, Jing; Niu, Wenyi; Wu, Yangfeng; MacGregor, Graham
Abstract : Objective: To study the effect of salt reduction on iodine status and to determine whether iodine consumption was still adequate after salt intake was reduced by ≈25% in northern China where universal salt iodisation is mandatory. Design and method: We measured 24 h urinary iodine in individuals who participated in School-EduSalt (School-based Education Programme to Reduce Salt), a cluster randomised controlled trial in 28 primary schools (279 children, age 10.1 ± 0.5 (SD), and 553 adults, age 43.8 ± 12.2). Children were educated about the harmful effects of salt on health and how to reduce salt intake during their usual health education lessons. Children then instructed their families to reduce salt consumption. The intervention duration was one school term (≈3.5 months). Results: At baseline, the mean salt intake was 7.0 ± 2.5 g/d in children and 11.7 ± 4.4 g/d in adults and the median iodine intake was 165.1 μg/d (IQR: 122.6–216.7) and 280.7 μg/d (IQR:205.1–380.9) in children and adults respectively. At the end of the study, both salt and iodine decreased in the intervention compared with control group. The mean effect on salt for intervention vs control was -1.9 g/d (95% CI: −2.6 to −1.3) in children and -2.9 g/d (95% CI: −3.7 to −2.2) in adults. The mean effect on iodine was −19.3% (95%CI: −29.4% to −7.7%) in children and -11.4% (95%CI: −20.3% to −1.5%) in adults. Conclusions: Our study, for the first time, has assessed salt and iodine intake by repeat 24 h urine collections. The School-EduSalt programme successfully reduced salt intake by ≈25% in both children and adults. Despite there being an accompany reduction in iodine, the median iodine intake was still adequate and well above the estimated average requirement for both children and adults. Our findings indicate that the WHO's salt target of 30% reduction by 2025 can be achieved without compromising iodine status.